2007
DOI: 10.2151/sola.2007-026
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Water-Vapor Field over the Kanto District Associated with Summer Thunderstorm Activities

Abstract: Characteristics of the water-vapor field in relation to thunderstorms on summer days over the Kanto district in Japan were studied, using precipitable water-vapor (PWV) derived from GPS during 2001 2005. PWV averaged on the active thunderstorm days showed distinct diurnal variation. In general, hourly data showed that PWV maximum appeared 1 2 hours prior to the maximum thunderstorm activity (precipitation or cloud to ground stroke). The increase of PWV in the mountainous region of northern Kanto coincided well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…GEONET studies have reported that water vapor variations precede initiations of moist convections (Seko et al 2007;Inoue and Inoue 2007). However, the horizontal resolution of GEONET is not high enough to capture the fine structure of a water vapor field associated with a convection cell since the horizontal scale of isolated convection is on the order of a couple of km.…”
Section: Introductionmentioning
confidence: 99%
“…GEONET studies have reported that water vapor variations precede initiations of moist convections (Seko et al 2007;Inoue and Inoue 2007). However, the horizontal resolution of GEONET is not high enough to capture the fine structure of a water vapor field associated with a convection cell since the horizontal scale of isolated convection is on the order of a couple of km.…”
Section: Introductionmentioning
confidence: 99%
“…Existing networks (not specifically designed for meteorological purposes) and specifically designed dense GNSS networks have been used for monitoring the distribution of water vapor in the atmosphere, with particular reference to its lower layer, that is, the troposphere. At least three different approaches have been applied: (1) investigation of the vertical column over a single station (Rocken et al 1997), (2) exploitation of existing national GNSS networks (Seko et al 2007;Inoue and Inoue 2007), and (3) implementation of specifically designed dense and hyperdense GNSS networks (Zhang et al 2008;Realini et al 2012;Sato et al 2013;Tsuda et al 2013;Oigawa et al 2015). In all aforementioned studies, which are surely not exhaustive, the water vapor content was monitored to support weather forecasting, which is useful for interpreting severe meteorological events.…”
Section: Gnss Meteorology: State Of the Artmentioning
confidence: 99%
“…The GEONET network includes more than 1300 stations throughout Japan, with an average spacing of approximately 20 km. The main purpose of the network is the monitoring of crustal deformation; however, it has a high potential as a meteorological sensor (Shoji 2009) and was used in several meteorological applications (e.g., Seko et al 2007;Inoue and Inoue 2007). The GEONET-derived PWV has been used for mesoscale analyses since 2009.…”
Section: Gnss Meteorology: State Of the Artmentioning
confidence: 99%
“…Niimura et al (2000) contended that the saturation information for the entire atmosphere provided by GPS PWV agrees well with stratiform rain, but that the relation becomes unclear with localized strong rain. In their statistical study, Inoue and Inoue (2007) found that the maximum PWV was observed 15̶30 min prior to the maximum CG stroke for only 40% of the observed thunderstorms. Thus, other discriminant criteria are needed for the remaining 60%.…”
Section: Introductionmentioning
confidence: 98%
“…They concluded that this threshold is associated with the averaged humidity of the entire atmosphere above the observation point, and that PWV provides information on the degree of saturation of the entire atmosphere. Inoue and Inoue (2007) conducted a statistical study to investigate the characteristics of the two-dimensional GPS-derived PWV field in relation to thunderstorms on summer days over the Kanto district. In many cases, both PWV and its 30 min increments indicated large values within an hour before a cloudto-ground (CG) stroke.…”
Section: Introductionmentioning
confidence: 99%